2011
DOI: 10.1007/s10750-011-0680-x
|View full text |Cite
|
Sign up to set email alerts
|

Mesograzers prefer mostly native seaweeds over the invasive brown seaweed Sargassum muticum

Abstract: Introduced algae form globally an increasing problem. Grazing on invaders could provide communities with resistance to algal invasions. In this study, we experimentally tested the food choice of mesoherbivores for native macroalgae versus the invader Sargassum muticum. We performed food choice experiments with common grazers (Gammarus insensibilis, Hydrobia ulvae and Stenosoma nadejda) and both the brown algal invader Sargassum muticum and its native macroalgal competitors, from both the south (Cystoseira humi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 64 publications
1
21
0
1
Order By: Relevance
“…The latter suggests that non-native plants experience less herbivory, because they (a) left their coevolved consumers behind and (b) herbivores in the recipient environment fail to recognize them as a food source. The suggestion that non-native species are less attractive for herbivores than native species has been tested for mesoand macrograzer consumption of marine macroalgae in several laboratory experiments [54][55][56]. Although the outcomes were in the most cases ambiguous, the studies showed that grazers frequently prefer native over nonnative algal species-what was again confirmed by the results of this study.…”
Section: Discussionsupporting
confidence: 76%
“…The latter suggests that non-native plants experience less herbivory, because they (a) left their coevolved consumers behind and (b) herbivores in the recipient environment fail to recognize them as a food source. The suggestion that non-native species are less attractive for herbivores than native species has been tested for mesoand macrograzer consumption of marine macroalgae in several laboratory experiments [54][55][56]. Although the outcomes were in the most cases ambiguous, the studies showed that grazers frequently prefer native over nonnative algal species-what was again confirmed by the results of this study.…”
Section: Discussionsupporting
confidence: 76%
“…data AE Engelen) and northern study site [33], respectively. Moreover, growth rates are similar in both seaweed species, along with palatability to the isopod S. nadeja [34]. Second, both species may use constitutive defences, although fast growing plants are predicted to invest less in constitutive defences than slower-growing plants [22].…”
Section: Discussionmentioning
confidence: 95%
“…; Forslund, WikstrĂśm & Pavia ; Engelen et al . ; Hammann et al . ), while little is known about the interactions between non‐native basibionts and resident epibionts (Strong, Maggs & Johnson ; Baer & Stengel ).…”
Section: Introductionmentioning
confidence: 99%